PERAN TEKNOLOGI INFORMASI DALAM MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN LPD DI KECAMATAN MENGWI, BADUNG - Manuari, Ida Ayu Ratih; Cahyadi Putra, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p09, 2023)
This research set out to test the hypothesis that LPDs in Badung's Mengwi District would have better financial reports if their managers had a better grasp of employee accounting, the value of ethical leadership, and the importance of a regulatory body. Partial Least Squares (PLS) analysis was applied on a total of 38 (thirty eight) research samples drawn from a census or saturation sample. The study discovered that accounting knowledge of the employees had an impact on the quality of the financial reports they produced, but that ethical leadership, the role of the supervisory body, and IT were unable to have an impact on the quality of the financial reports produced by LPDs.